Changing Life Value and Demographic Change in Contemporary Japanese Society - Moriyama, Mikihiro (UI Scholars Hub, 2019)
Japan has experienced a rapid decrease in population. The main reason for this distorted demography (called Shoushi Koureika in Japanese) has been caused by a reduction in the number of children. Another reason is the extension of human lifespan. This rapid demographic change has caused social issues such as lack of workforce, an increase in the social security revenue and a reduction in the number of schools. The Japanese government has tackled these social problems and its effort has had an effect to some extent, but the hard work needs to continue. In this article, I try to explore reasons for the social issues and problems by focusing not only on changes in the social conditions but also on changes in the life value of Japanese people. Some possible solutions for the social issues and problems can be suggested for the coming decades in Japan. In particular, I try to explore solutions that are compatible with Japanese society to alleviate the problems.